An improved parametric method for evaluating radiative accelerations in stellar interiors. Issue 3 (26th August 2020) - Alecian, G; LeBlanc, F
ABSTRACT: The single-valued parameter (SVP) method is a parametric method that offers the possibility of computing radiative accelerations in stellar interiors much faster than other methods. It has been implemented in a few stellar evolution numerical codes for about a decade. In this paper, we describe improvements we have recently brought in the process of preparing, from atomic/opacity data bases, the SVP tables that are needed to use the method, and their extension to a larger stellar mass domain (from 1 to 10 solar mass) on the main sequence. We discuss the validity domain of the method. We also present the website from where new tables and codes can be freely accessed and implemented in stellar evolution codes.